Identification and characterization of a Babesia bigemina thrombospondin-related superfamily member, TRAP-1 : a novel antigen containing neutralizing epitopes involved in merozoite invasion - Montenegro, Valeria Noely; Paoletta, Martina; Jaramillo Ortiz, Jose; Suarez, Carlos Esteban; Wilkowsky, Silvina Elizabeth (BioMed Central, 2021)
Background: Thrombospondin-related anonymous protein (TRAP) has been described as a potential vaccine candidate for several diseases caused by apicomplexan parasites. However, this protein and members of this family have not yet been characterized in Babesia bigemina, one of the most prevalent species causing bovine babesiosis. Methods: The 3186-bp Babesia bigemina TRAP-1 (BbiTRAP-1) gene was identified by a bioinformatics search using the B. bovis TRAP-1 sequence. Members of the TRAP and TRAP-related protein families (TRP) were identified in Babesia and Theileria through a search of the TSP-1 adhesive domain, which is the hallmark motif in both proteins. Structural modeling and phylogenetic analysis were performed with the identified TRAP proteins. A truncated recombinant BbiTRAP-1 that migrates at approximately 107 kDa and specific antisera were produced and used in Western blot analysis and indirect fluorescent antibody tests (IFAT). B-cell epitopes with neutralizing activity in BbiTRAP-1 were defined by enzyme-linked immunosorbent assays (ELISA) and invasion assays. Results: Three members of the TRAP family of proteins were identified in B. bigemina (BbiTRAP-1 to -3). All are type 1 transmembrane proteins containing the von Willebrand factor A (vWFA), thrombospondin type 1 (TSP-1), and cytoplasmic C-terminus domains, as well as transmembrane regions. The BbiTRAP-1 predicted structure also contains a metal ion-dependent adhesion site for interaction with the host cell. The TRP family in Babesia and Theileria species contains the canonical TSP-1 domain but lacks the vWFA domain and together with TRAP define a novel gene superfamily. A variable number of tandem repeat units are present in BbiTRAP-1 and could be used for strain genotyping. Western blot and IFAT analysis confirmed the expression of BbiTRAP-1 by blood-stage parasites. Partial recognition by a panel of sera from B. bigemina-infected cattle in ELISAs using truncated BbiTRAP-1 suggests that this protein is not an immunodominant antigen. Additionally, bovine anti-recombinant BbiTRAP-1 antibodies were found to be capable of neutralizing merozoite invasion in vitro. Conclusions: We have identified the TRAP and TRP gene families in several Babesia and Theileria species and characterized BbiTRAP-1 as a novel antigen of B. bigemina. The functional relevance and presence of neutralization-sensitive B-cell epitopes suggest that BbiTRAP-1 could be included in tests for future vaccine candidates against B. bigemina.